2018
DOI: 10.12688/f1000research.17006.1
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and emotional issues among primary school pupils with congenital colour vision deficiency in the Federal Territory of Kuala Lumpur, Malaysia: A case-control study

Abstract: Background: Congenital colour vision deficiency (CCVD) is an untreatable disorder which has lifelong consequences. Increasing use of colours in schools has raised concern for pupils with CCVD. This case-control study was conducted to compare behavioural and emotional issues among age, gender and class-matched pupils with CCVD and normal colour vision (NCV). Methods: A total of 1732 pupils from 10 primary schools in the Federal Territory of Kuala Lumpur were screened, of which 46 pupils (45 males and 1 female) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The CVD prevalence between undergraduate (2.54%) and postgraduate (1.85%) in our study was significantly different. The results of the impact of CVD on academic performance form previous studies were inconsistent [6,[15][16][17][18] . Some studies found that there was no significant difference between CVD students and normal students in academic performance.…”
Section: Discussionmentioning
confidence: 79%
“…The CVD prevalence between undergraduate (2.54%) and postgraduate (1.85%) in our study was significantly different. The results of the impact of CVD on academic performance form previous studies were inconsistent [6,[15][16][17][18] . Some studies found that there was no significant difference between CVD students and normal students in academic performance.…”
Section: Discussionmentioning
confidence: 79%
“…Further, there are few studies with Low prevalence rate, like 3.8% in (Niroula and Saha, 2010), 2.1% in (Shrestha et al, 2010), 2.6% in (Tabansi et al, 2008), 2.5% in (Oduntan et al, 2019), 2.3% in (Ugalahi et al, 2016). Some Studies had a higher prevalence rate like 5.4% in (Chia et al, 2008),4.9% in (Thomas et al, 2018). The variation in the results between our study and other studies is mainly due to heterogeneity of study population, Study area (Geographical location), and Screening methodologies used for the colour vision test.…”
Section: Discussionmentioning
confidence: 99%
“…We plan to explore ColourSpot's ability to classify protan and deutan CVD types by testing it in adults and older children against the anomaloscope. We aim that accurate diagnosis of CVD using ColourSpot from 4 years of age at the start of education will mitigate some of the negative impact of CVD on children's education and well-being (Grassivaro Gallo et al, 1998Gallo et al, , 2002Mehta et al, 2018;Suero et al, 2005;Thomas et al, 2018;Thuline, 1964). The ColourSpot app provides advice sheets on CVD, designed by Colour Blind Awareness, a non-profit organization to raise awareness of CVD (http://colourblindawareness.org), which aims to help parents and teachers adopt strategies to mitigate some of the potential negative effects of CVD on children.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to detect CVD and identify how individuals can be supported, as it can significantly affect quality of life such as health, well-being and work (Barry et al, 2017;Chan et al, 2014;Cole, 2004Cole, , 2007Cumberland et al, 2005;Steward & Cole, 1989;Tagarelli et al, 2004). Ninety percent of adults with CVD encounter problems in their daily lives (Steward & Cole, 1989), while children with CVD are at risk of social, behavioral and emotional difficulties, and adverse educational outcomes (Grassivaro Gallo et al, 1998Gallo et al, , 2002Suero et al, 2005;Thomas et al, 2018;Thuline, 1964). Educational materials, especially those for young children, such as reading schemes or mathematics activities (Birch, 2001), typically rely on color as a learning tool (Rinaldi et al, 2020;Suero et al, 2005), which makes them less accessible for children with CVD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation